Cuidados de enfermería en pacientes extubados en unidad de cuidados intensivos, revisión sistemática. - Velasco Villarreal, Evelyn Gianella (2024)
The systematic review focused on identifying the most effective nursing interventions in the post-extubation phase of critically ill patients. Objective: Identify nursing care in extubated patients in the intensive care unit. Materials and methods: The method applied was a systematic review of order in a sample that includes 175 analyzed studies, of which 16 were chosen for the present investigation. The analysis of multiple studies revealed the importance of exhaustive monitoring of physiological variables such as respiratory rate. , oxygen saturation and spontaneous ventilatory patterns. Adequate airway management, including aspiration of secretions and oral hygiene, was essential to prevent infectious and obstructive complications. Likewise, the relevance of gradual and personalized respiratory weaning, pain and anxiety management was highlighted. Optimal patient positioning, early mobilization, respiratory physiotherapy. Conclusion The results underscore the need for a multifactorial approach that considers the individual characteristics of each patient and the implementation of standardized care protocols. However, methodological limitations were identified in the included studies, such as heterogeneity in interventions and results, suggesting the need for future research with more vigorous methodological designs to strengthen scientific evidence in this field. In conclusion, this systematic review provides a solid basis for the development of evidence based clinical practice guidelines and contributes to improving the quality of nursing care in the posttubation phase